دراسة انعكاسية مركبات السيلينيت من النوع Bi12MO20 (M= Si, Ge, Ti) - صارم, عمّار; خلاص, طلال (Latakia University Journal -Basic Sciences Series, 2018)
Three sillenite compounds Bi12MO20 (M=Si, Ge, Ti) were synthesized, and the resulting single-phase crystals were then investigated in the energy range from 1.5 to 6eV at room temperature by reflectance method. A rich structure corresponding to the optical interband transitions were observed in the reflectivity spectra. The electronic band structure of modification of sillenite compounds resulting from the above data is analyzed and discussed. An analysis of the optical properties of the Bi12MO20 (M=Si, Ge, Ti) single crystals has been correlated with the structure of the bismuth-oxygen network of the sillenite crystals. The optical transitions occur at the saddle points on the G-P(L) line. The probability of transitions at the P and H points is low, because of the density of states is expected to be low there. The results contribute to the model of the electronic structure of these materials. تم تصنيع ثلاثة مركبات من النوع Bi12MO20 (M = Si, Ge, Ti)، ثم اختبرت البلورات الناتجة أحادية الطور في مجال الطاقة من 1.5 إلى 6 إلكترون فولت عند درجة حرارة الغرفة بوساطة طريقة الانعكاسية. لوحظت في أطياف الانعكاسية بنية غنية مطابقة إلى الانتقالات الضوئية ما بين الحزم. نوقشت وحللت من المعطيات السابقة تغيرات بنية الحزم الإلكترونية في مركبات السيلينيت. تم ربط تحليل الخواص الضوئية للبلورات الأحادية Bi12MO20 (M = Si, Ge, Ti) مع بنية الشبكة بزموث - أكسجين في بلورات السيلينيت. وإن الانتقالات الضوئية تحدث عند النقاط السرجية على المستقيم G-P(L). واحتمال الانتقالات الضوئية عند النقطتين P و H منخفض، لأنه يتوقع أن تكون كثافة الحالات عندهما منخفضة. وإن هذه النتائج ساهمت في نموذج البنية الالكترونية لهذه المواد.